Reverse Taxonomy and Phylogenetic‐Phylogenomic Inferences Clear the Fog on the Northeastern Atlantic‐Mediterranean Eurynome and Resurrect the Family Eurynomidae (Decapoda: Majoidea) - Valentina Tanduo; Paolo Fasciglione; Giuliano Giacobelli; Lucia Rizzo; Fabio Crocetta (Zoologica Scripta, 2026)
Spider crabs of the genus Eurynome have complex taxonomic, phylogenetic, and biogeographic histories worldwide. Using newly generated molecular data, including the characterization of complete mitochondrial genomes, we addressed several unresolved questions surrounding the genus and its two Atlantic‐Mediterranean representatives, the type species Eurynome aspera and its sympatric Eurynome spinosa . DNA‐barcoding and reverse taxonomy demonstrated conspecificity between Atlantic and Mediterranean samples, confirmed the occurrence of E. spinosa in the Mediterranean Sea sensu stricto , and contradicted most diagnostic characters previously proposed in the literature. In their place, a set of 10 molecularly validated morphological traits, regardless of sex and developmental stage, was proposed and accompanied by high‐resolution imagery. The DNA‐assayed material was then used to investigate the phylogenetic position of Eurynome through various inferences (multilocus and mitochondrial genome trees, and mitochondrial gene orders), which suggested that these taxa form a distinct, early‐diverging clade, for which the family Eurynomidae Neumann, 1878 is resurrected here. This was also supported by high similarity with the ancestral Brachyura mitochondrial gene order and strong dissimilarities with other majoid ones. Although several questions remain open, the present results resolve debates on two pseudo‐cryptic species, elevate Eurynome to one of the most molecularly characterized majoid genera, and lay a solid foundation for proceeding with the study of allied taxa and the entire superfamily through modern integrative approaches.

New records of marine biodiversity in the Mediterranean Sea (April 2026) - ARGYRO ZENETOS; FARES NASSER ABD EL-GWAAD; AHMED MOHAMED AL-BEAK; MOUNA ANTIT; YACOPO BALDACCHINO; CLAUDIO BARRÍA; ILIJA ĆETKOVIĆ; MAURIZIO COSTA; FABIO CROCETTA; NIKOLA ĐORĐEVIĆ; AMANI FITORI; BELLA S. GALIL; et al. (Mediterranean Marine Science, 2026)
This collective article presents new information about 18 species occurring in 12 Mediterranean countries from the Alboran Sea to the Levantine Sea. Five lessepsian species namely Erugosquilla massavensis, Syrnola fasciata, Plocamopherus ocellatus, Maritigrella fuscopunctata and Siganus javus have spread within 2025 to neighbouring MSFD areas. Another five are here reported as first country records [Polyandrocarpa zorritensis (Malta), Gonioinfradens giardi (Italy), Istiblennius meleagris (Egypt), Epinephelus fasciatus (Israel), Lophocladia trichoclados (Montenegro)]. Cladophora patentiramea has spread from the Levantine to the Aegean Sea, while Pinctada radiata has reached Granada, and Cádiz. The Atlantic fish Enchelycore anatina and Synodus synodus have expanded their distribution to Montenegro and Syria respectively. Three rare native species are reported for first time at country level, while a fourth (Mobula birostris) has made an appearance more than a century after its first Mediterranean record.

Marine non-indigenous species of Cyprus: pathways, introduction dynamics, spatial patterns, and policy implications - Christina Michail; Fabio Crocetta; Argyro Zenetos; Joachim Langeneck; Konstantinos Tsiamis; Francesco Tiralongo; Demetris Kletou; George Constantinou; Leda L. Cai; Lavrentiοs Vasiliades; Maria Rousou; Stelios Katsanevakis; et al. (Biological Invasions, 2026)

New records of rarely reported species in the Mediterranean Sea (December 2025) - MARGHERITA TOMA; DARYL AGIUS; ERNESTO AZZURRO; MARZIA BO; FABIO CROCETTA; İSMAIL DAL; TOMMASO DELLI CARRI; MEHMET CENGIZ DEVAL; LORIS GALLI; ANDROMACHI GKOULIA; FABIO GRATI; DEMETRIS KOLOKOTRONIS; et al. (Mediterranean Marine Science, 2025)
New records of rarely reported species in the Mediterranean Sea (December 2025)

The flow of non-indigenous species continues in the north Adriatic Sea: Cerastoderma edule and Mytilopsis leucophaeata (Mollusca: Bivalvia) are invading the Sacca di Goro lagoon - Giuliano Giacobelli; Valentina Tanduo; Marco Orlandi; Edoardo Turolla; Fabio Crocetta (Zoologischer Anzeiger, 2025)

New records of rarely reported species in the Mediterranean Sea (March 2025) - JOSÉ CARLOS BÁEZ; OKAN AKYOL; ERNESTO AZZURRO; PIETRO BATTAGLIA; ANGEL BELMONTE-GALLEGOS; GEORGIOS CHRISTIDIS; FABIO CROCETTA; CEM DALYAN; YUNUS GÖNÜL; FABIO GRATI; SILVESTRO GRECO; CHRYSOULA GUBILI; et al. (Mediterranean Marine Science, 2025)
This collective study presents information on fifteen (15) species recorded across five countries (Greece, Italy, Slovenia, Spain, and Türkiye) and four (4) ecoregions, ranging from the Alboran Sea to the Aegean Sea. The recorded species belong to three phyla: Mollusca (3 species), Arthropoda (3 species), and Chordata (9 species). Among mollusks, Martadoris mediterranea is reported for the first time in the Aegean Sea at two different locations, while Opisthoteuthis calypso and Octopoteuthis sicula are newly recorded in the western Mediterranean. Regarding arthropods, Ocypode cursor is reported from the Tyrrhenian coast of Sicily, Pachygrapsus transversus is recorded for the first time in the Tyrrhenian Sea, and Cancer pagurus in the Sea of Marmara. Among chordates, Lobotes surinamensis and Zu cristatus are newly recorded in the Alboran Sea, while Callionymus fasciatus and Symphodus doderleini are reported from Slovenian coastal waters. Tripterygion delaisi and Gymnothorax unicolor are documented for the first time in the waters of the Sea of Marmara and Crete, respectively. Additionally, new records of rarely reported fish species include Arctozenus risso, Chromogobius zebratus, and Epinephelus aeneus in Turkish, Spanish, and Italian waters, respectively.

Engagement of fishers in citizen science enhances the knowledge on alien decapods in Cyprus (eastern Mediterranean Sea) - Christina Michail; Valentina Tanduo; Fabio Crocetta; Ioannis Giovos; Sofia Litsiou; Periklis Kleitou (Aquatic Ecology, 2024)

New records of introduced species in the Mediterranean Sea (November 2023) - JOACHIM LANGENECK; RIGERS BAKIU; NIKOLETTA CHALARI; GEORGIOS CHATZIGEORGIOU; FABIO CROCETTA; SERVET AHMET DOĞDU; SHERIF DURMISHAJ; BELLA GALIL S.; JOSÉ ANTONIO GARCÍA-CHARTON; ANIL GÜLŞAHIN; RAZY HOFFMAN; AGOSTINO LEONE; et al. (Mediterranean Marine Science, 2023)
This collective article presents new information about 15 introduced taxa belonging to five phyla: one Rhodophyta, one Chlorophyta, one Mollusca, one Annelida, two Arthropoda, and nine Chordata (one Ascidiacea and eight Osteichthyes). The records refer to eight Mediterranean countries and extend from the Alboran Sea to the Levantine Sea as follows: Spain: first record of the African hind Cephalopholis taeniops for the Alboran Sea, and a further record of the Monrovia surgeonfish Acanthurus monroviae, extending its distribution northwards in the Western Mediterranean. Italy: an additional record of the squat lobster Scyllarus subarctus based on its nisto stage, new records of the lionfish Pterois miles in the north-western Ionian Sea, first records of the bivalve Fulvia fragilis for the Italian Adriatic coast, and a record of the amphipod Ptilohyale littoralis in the northern Adriatic Sea, also representing the first report for the Mediterranean Sea. Montenegro: first record of the non indigenous ascidian Ciona robusta. Albania: first record of the red cornetfish Fistularia petimba. Greece: first record of the cryptogenic polychaete Alitta succinea in association with ship fouling, suggesting the possibility of a non-indigenous origin of Mediterranean populations of this species, and first record of the Seychelles dragonet Synchiropus sechellensis for the Saronikos Gulf. Türkiye: first record of the red alga Womersleyella setacea, report of an abundant population of the Indian twospot cardinalfish Cheilodipterus novemstriatus in the Turkish Aegean Sea, and first record of Synodus randalli, also corresponding to the first report for the Mediterranean Sea. Syria: first record of the blenny Istiblennius cf. meleagris. Israel: report of an algal bloom of the green alga Codium parvulum, and first record of Synchiropus sechellensis.

Tackling bioinvasions in commercially exploitable species through interdisciplinary approaches: A case study on blue crabs in Africa's Mediterranean coast (Bizerte Lagoon, Tunisia) - Mouna Rifi; Leila Basti; Lucia Rizzo; Valentina Tanduo; Adriana Radulovici; Sabri Jaziri; İrfan Uysal; Nihel Souissi; Zeineb Mekki; Fabio Crocetta (Estuarine, Coastal and Shelf Science, 2023)

The Miseno Lake (Central-Western Mediterranean Sea): An Overlooked Reservoir of Non-Indigenous and Cryptogenic Ascidians in a Marine Reserve - Riccardo Virgili; Valentina Tanduo; Stelios Katsanevakis; Francesco Terlizzi; Guido Villani; Angelo Fontana; Fabio Crocetta (Frontiers in Marine Science, 2022)
Ascidians are the largest and most diverse class of the subphylum Tunicata, and are important components of marine benthic communities. They are also renowned worldwide invaders, of growing concern due to ease of spread and impacts on native biota. We hereby combined bathymetric and habitat mapping, extensive transect and photo-quadrat sampling, and a morphological and molecular study on selected specimens to evaluate taxonomic composition, cover, and distribution pattern of ascidians in a marine reserve of the central-western Mediterranean Sea, the Miseno Lake (Bacoli, Naples, Italy). Twenty-four taxa were found, of which 9 were non-indigenous species (NIS), 5 cryptogenic, and 10 native, delineating the Miseno Lake as a major hotspot of NIS and cryptogenic ascidians. DNA barcoding yielded 114 sequences, confirming identification for 22 taxa but also revealing single to few mismatches per species. Taxonomic insights were offered in the text and the Supplementary Material for several taxa, including the understudied Ascidia colleta and Ascidia malaca . The presence of a new clade was discovered in the Distaplia bermudensis species complex. Didemnum pseudovexillum and Polyclinum constellatum were respectively first recorded in Italy and western Mediterranean, and the same holds true for other taxa whose accurate identification was only possible through molecular evidence. The analysis of photographic archives allowed backdating and georeferencing to the Miseno Lake of the first records of Aplidium accarense and Botrylloides niger in Italy and of P. constellatum in the Mediterranean. Generalized Additive Models revealed that the abundance of NIS increased with availability of hard substrates (rocks or litter), decreased with depth, and was the highest in the channels connecting to other water bodies, followed by the peripheral areas of the lake. No certain evidence of competitive restriction of native ascidians was found. Finally, introduction pathways, potential impacts, and additional insights were discussed for NIS. The present study provides a baseline to evaluate shifts in the ascidian communities in the future, suggests that constant monitoring programs constitute crucial steps to achieve solid NIS management, and confirms marine reserves as widely vulnerable to biological invasions, especially when they coincide with potential hotspots of arrival or spreading such as semi-enclosed basins.

Untargeted Metabolomics Yields Insights Into the Lipidome of Botrylloides niger Herdman, 1886, An Ascidian Invading the Mediterranean Sea - Gerardo Della Sala; Daniela Coppola; Riccardo Virgili; Giovanni Andrea Vitale; Valentina Tanduo; Roberta Teta; Fabio Crocetta; Donatella de Pascale (Frontiers in Marine Science, 2022)
Human-mediated dispersal of alien species in new biogeographic realms is one of the major drivers of biodiversity change in marine ecosystems. Among others, ascidians are invasive species spreading worldwide, thus causing ecological and economic harms in the recipient environments. An integrated taxonomic approach on selected samples allowed the identification of Botrylloides niger Herdman 1886 as a non-indigenous ascidian forming large aggregates and outcompeting native species in the Fusaro Lake (central-western Mediterranean Sea). This led to the opportunity to investigate in deep its metabolome for the first time. Untargeted mass spectrometry-based metabolomics unveiled B. niger to be a source of nutraceuticals and bioactive natural products, such as lysophospholipids, sulfonolipids, polyunsaturated fatty acids, sphingolipids, monoacylglycerols, and alkaloids. Even if causing ecosystem alterations, our results suggest that B. niger could be exploited for nutritional and/or pharmaceutical purposes, thereby turning a treat in a resource.

Hiding in Fouling Communities: A Native Spider Crab Decorating with a Cryptogenic Bryozoan in a Mediterranean Marina - Valentina Tanduo; Riccardo Virgili; David Osca; Fabio Crocetta (Journal of Marine Science and Engineering, 2021)
Camouflage is the method by which animals conceal by blending in with the environment, and may be achieved by fixed or changing color, shape, texture, chemical secretions, and/or behavior [...]

Protect the Natives to Combat the Aliens: Could Octopus vulgaris Cuvier, 1797 Be a Natural Agent for the Control of the Lionfish Invasion in the Mediterranean Sea? - Fabio Crocetta; Maria Shokouros-Oskarsson; Nikolaos Doumpas; Ioannis Giovos; Stefanos Kalogirou; Joachim Langeneck; Valentina Tanduo; Francesco Tiralongo; Riccardo Virgili; Periklis Kleitou (Journal of Marine Science and Engineering, 2021)
Biological invasions constitute a major threat to native ecosystems and to global biodiversity [...]

The Indo-Pacific Sergeant Abudefduf vaigiensis (Quoy & Gaimard, 1825) (Perciformes: Pomacentridae) in Libya, South-Central Mediterranean Sea - David Osca; Valentina Tanduo; Francesco Tiralongo; Ioannis Giovos; Sara A. A. Almabruk; Fabio Crocetta; Jamila Rizgalla (Journal of Marine Science and Engineering, 2019)
The Indo-Pacific Sergeant Abudefduf vaigiensis (Quoy & Gaimard, 1825) (Chordata: Pisces: Actinopterygii: Perciformes: Pomacentridae) is first recorded in the south-central Mediterranean Sea (Libya), based on the external morphology and the barcoding of a fragment of the cytochrome c oxidase subunit I gene. Present sightings from field surveys and social media include juveniles, sub-adults, and a single adult specimen, suggesting that the species is now established in Libyan waters. No certainties occur regarding timing and possible pathway of arrival of this species in the area, and it may have simply gone undetected for years. The joint effort of field studies and citizen science projects in collaboration with international organizations continues shedding light on bioinvasions in Libya, with valuable outcomes for the Mediterranean marine biology as a whole.